Factors affecting the wellbeing of mid-achieving university students: a case study from China - Zou, Dandan; Lin, Zitong; Chen, Chen; Yu, Huiying (Frontiers in Psychology, 2024)
Background The study aims to investigate the wellbeing of mid-achieving university students on campus and the factors affecting it. Given that this group represents a large yet often overlooked portion of higher education, the study endeavors to analyze the specific factors affecting their wellbeing to provide insights to foster a more comprehensive and inclusive educational environment. Methodology The study adopted a qualitative research method. A total of 30 mid-achieving university students from different departments at Guizhou Medical University in China were interviewed in-depth. The interviews were conducted via the online WeChat platform from 1st March 2024 to 13th September 2024. The semi-structured interviews focused on “moments in campus life that make mid-achieving university students feel happy or joyful.” All interviews were audio-recorded and transcribed into text, which was thoroughly coded and analyzed by the researcher using NVIVO 12 software to comprehensively assess the multiple factors that affect the wellbeing of students. Results The wellbeing of mid-achieving university students is affected by a combination of factors, including freedom and autonomy, social interactions, collective activities, campus environment and facilities, and academic achievement. Conclusion Enhancing the autonomy of mid-achieving university students can significantly improve their self-efficacy and overall wellbeing. While social interactions and collective activities provide emotional support, they also present interpersonal challenges. Sufficient recreational spaces and a diverse range of food options on campus can help alleviate students’ stress and increase their satisfaction with campus services. Conversely, policies banning motorized bicycles may negatively affect students’ sense of wellbeing. Theoretically, the study contributes to the literature on student wellbeing in higher education psychology, particularly by offering a deeper understanding of the large but often neglected group of mid-achieving students. Practically, the findings emphasize the importance of creating more supportive and responsive educational environments tailored to the needs of these students, thereby facilitating inclusive campus environments and fully harnessing the learning potential of mid-achieving students. The study also proposes specific improvement strategies, such as optimizing campus facilities, enhancing student autonomy, and bolstering social and academic support systems. These measures are expected to directly improve the daily experiences of mid-achieving students and enhance their overall wellbeing.